2006
DOI: 10.1021/bi0609624
|View full text |Cite
|
Sign up to set email alerts
|

The Transferable Tail:  Fusion of the N-Terminal Acidic Extension of Heparin Cofactor II to α1-Proteinase Inhibitor M358R Specifically Increases the Rate of Thrombin Inhibition

Abstract: The conversion of the reactive center bond of the serpin alpha1-proteinase inhibitor (alpha1-PI, also known as alpha1-antitrypsin) from Met-Ser to Arg-Ser decreases the rate at which it inhibits neutrophil elastase and endows it with the ability to inhibit thrombin and activated protein C (APC). Another serpin, heparin cofactor II (HCII), contains a unique N-terminal extension that binds thrombin exosite 1. We fused residues 1-75 of HCII to the N-terminus of alpha1-PI M358R, forming an HCII-alpha1-PI chimera (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(52 citation statements)
references
References 38 publications
6
45
1
Order By: Relevance
“…We have previously reported that API made in this soluble, intracellular bacterial expression system, exhibits SI values of 2–3[29], [30], [41]. Others employing different bacterial expression systems, some in which recombinant API was renatured from inclusion bodies, have reported SI values closer to unity [55], [56].…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…We have previously reported that API made in this soluble, intracellular bacterial expression system, exhibits SI values of 2–3[29], [30], [41]. Others employing different bacterial expression systems, some in which recombinant API was renatured from inclusion bodies, have reported SI values closer to unity [55], [56].…”
Section: Discussionmentioning
confidence: 76%
“…The rate of reaction of recombinant API proteins was quantified by determining the second order rate constant (k 2 ) of thrombin inhibition in a discontinuous assay, under pseudo first order conditions, as in previous studies from this laboratory [29], [40], [41], as was the stoichiometry of inhibition (SI). The SI is the number of serpin molecules required to inhibit one protease molecule, and was determined as previously described, by reacting various ratios of thrombin with API proteins, plotting the ratio versus the residual thrombin activity, and using linear regression to extrapolate to zero [29], [40], [41].…”
Section: Methodsmentioning
confidence: 99%
“…Previous work from this laboratory showed that fusion of residues 1-75 of HCII to the N-terminus of another thrombin inhibitory serpin, the M358R “Pittsburgh” variant of α 1 -proteinase inhibitor (α 1 -PI, also known as α 1 -antitrypsin) increased the rate of thrombin inhibition in the absence of GAGs by 21-fold [19]. The rate advantage of the HAPI M358R fusion protein over unfused α 1 -PI M358R was reduced to 6-fold when residues 55-75 were substituted for the entire N-terminal acidic extension, and eliminated altogether either when all acidic residues between 55-75 were neutralized by mutation in the full 1-75 transferred extension, or when residues 1-54 alone were employed for fusion [19].…”
Section: Introductionmentioning
confidence: 99%
“…5. Lysates containing API M358R exhibited a gradual increase in thrombin-bound API reactivity over 60 min, while two API M358R variants with additional mutations previously shown to enhance their rate of thrombin inhibition by 2- (Scott et al, 2014) to 19-fold (Sutherland et al, 2006) exhibited more rapid rates of thrombin binding that plateaued over time, and API T345R/M358R exhibited minimal, background levels of binding (Fig. 5).…”
Section: Effect Of Time Of Incubation With Thrombin On the Thrombin Cmentioning
confidence: 89%
“…Recombinant API proteins were characterized kinetically as thrombin inhibitors by determination of their pseudo-first order rate constant under appropriate order conditions (≥10-fold molar excess of API over thrombin in a two-stage assay) and division of that value by the initial API concentration to yield the second order rate constants (k 2 ) (Filion et al, 2004;Sheffield et al, 2012). Reaction stoichiometries (i.e., stoichiometries of inhibition, SI) were also determined as previously described (Sutherland et al, 2006).…”
Section: Expression Purification and Kinetic Characterization Of Rementioning
confidence: 99%